KOINTEGRASI DAN DAMPAK GUNCANGAN INVESTASI LUAR NEGERI TERHADAP EKONOMI AGRIBISNIS DI INDONESIA - Iwan Riswandi (Departemen Agribisnis, FEM-IPB, 2007)
The objectives of this research are: (1) to analyze co-integration of the Indonesian agribusiness economy and its international market, and (2) to analyze the impacts of foreign investment policies on Indonesian agribusiness economy. This research used time series econometric approach with the co-integration method of vector error correction model (VECM), referring to the procedure of Engle-Granger (1987) and Enders (1995) with the model of structural matrix equation of Pesaran and Smith (1998). The long term of the Indonesian agribusiness economy will be influenced by foreign investment shocks. Domestic expectation to the increases of household consumption, employment and farmers’ income will be determined by the changes of each own variables. The shocks impact will give positive influence on agribusiness economic variables in the short as well as in the long terms; except for employment, agribusiness productivity and farmers’ income.